Juridical Review Of Agreement And Adoption Law Due For Adopted Children When Adopted Parent Lift Divorce - Etik Kuswanti; Akhmad Khisni (Jurnal Akta, 2018)
Kids are important in human life, a lot of people who are expecting the presence of children as successor descent but some have not given credence to be given the baby. Adoption is an alternative to get around this problem. One polemics are legal consequences for adopted children when the father of the foster mother divorced. This study aims to determine hadhanah for adopted children when the father of the foster mother divorced. This research using normative juridical approach, ie an approach based on the decision of the Supreme Court, law and jurisprudence. The results show that the Islamic Law Compilation (KHI) stated position adopted child the same as biological children they both get Hadhanah, except in the case of nasab so do not get the inheritance, but was borrowed for adopted children as contained only one-third. In the case of child maintenance rights for the adopted child under age, the rights given to a foster mother, if an adult or child is old enough lift may choose to want to go with whom, nevertheless all maintenance fees charged to the adopted child's adoptive father. Custody and all the costs of the foster child needs to last until the adopted child an adult, independent or have been married. If the adopted child if the woman he would marry then it could be a guardian of marriage are biological parents or biological relatives. So although the adoptive mother divorced fathers still be obliged to maintain and educate the adopted child.Keywords: Judicial Review, Adoption, Legal Consequences, Divorce